The Relationship Between Contextual and Dispositional Variables, Well-Being and Hopelessness in School Context - Buzzai, Caterina; Sorrenti, Luana; Orecchio, Susanna; Marino, Davide; Filippello, Pina (Frontiers in Psychology, 2020)
The literature’s interest has been focused on the study of well-being or depression. However, there has been little research that investigates the relationship between well-being and hopelessness (HPL) and the underlying contextual and dispositional variables. Therefore, the aim of the present study was to examine the relationship between some contextual (need-supportive interpersonal behavior and need-thwarting interpersonal behavior) and dispositional variables (dispositional optimism, positive/negative affectivity, explanatory style), academic achievement, general well-being, and school HPL in adolescent students. The results showed that general well-being was positively predicted by need-supportive interpersonal behavior, dispositional optimism, positive affectivity, and adaptive explanatory style (attribution to commitment in the school context), while it was negatively predicted by negative affectivity. Meanwhile, school HPL was positively predicted by need-thwarting interpersonal behavior, negative affectivity, dysfunctional explanatory style (attribution to luck in the school context), while it was negatively predicted by attribution to commitment in the school context and academic achievement. These results provide useful data for the implementation of well-being promotion and school HPL prevention. The implications are discussed as follows.